Perception of Preclinical Medical Students About Pathology Subject and the Teaching Methods in an Indian Medical College - Sood S; Gulia SP (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2021)
Background: Pathology is a key subject at the pre-clinical stage of medical training. Objectives: To determine the perception of second-year MBBS (preclinical) students regarding Pathology as a subject and the effectiveness of various teaching, learning and assessment methods. Methods: This cross-sectional study was carried out on 145 randomly selected, second-year MBBS students, appearing for their Phase II final university exams. A predesigned questionnaire with questions about students' perception of pathology was administered to the students. The questionnaire also assessed the various teaching-learning methods currently used by the faculty. The students were also requested to make suggestions regarding the modifications needed in the teaching methods. Results: A total of 145 out of 150 regular-batch students participated in the study. One hundred (68.9%) regarded pathology as an interesting subject; 131 (90.3%) felt pathology acts as a bridge between paraclinical and clinical branches while 107 (73.8%) found blackboard teaching more effective. Conclusion: The study revealed that the preclinical medical students showed a favourable predisposition towards pathology as a subject while highlighting areas that need to be addressed for more effective teaching and improved learning towards producing better medical professionals.